The comparative validities of discrete-point and integrative tests of English proficiency - Castro, Corabella Surriga
The validity indices of two types of language test - the discrete-point and the integrative tests were compared in this study. Two sets of parallel tests, each consisting of 200 items, were constructed and divided into four booklets - A, B, C, and D. Booklets A and B contained discrete-point items, and booklets C and D had integrative test items. The following conclusions were gleaned from the study: that the discrete-point test was easier than the integrative test; and that the Integrative test scores correlate positively with discrete-point test scores and the Integrative test can be as reliable as discrete-point tests.